The Primeval Cosmic River and Its Ecological Realities: On the Curatorial Project Danube River School. Issue 2 (2nd July 2016) - Fowkes, Maja; Fowkes, Reuben
Abstract : As the longest river in the heart of the European continent, the Danube has been a recurrent topic for artists, writers, poets, filmmakers, and theorists, and whether their accounts linger in the national realm of one of the ten countries through which the river passes, or follow its transnational flow, Anthropocentric undercurrents can regularly be traced in their narratives. Uncovering the environmental history of the Danube, featuring river-centered artistic practices, and investigating the potential for an integrated ecological future of the river were at the core of the interdisciplinary curatorial project the River School, organized by the Translocal Institute between 2013 and 2015. This article investigates ecological challenges to the traditional cultural approaches to the Danube, which reflect the social and political logic that turns the river into a marker of geopolitical struggles, a route for conquest, and a delimiter of national territory, as well as a site for the expression of cultural supremacy. Focusing on the insights provided by the work of contemporary artists, also explored are the potential of the experiential aspect of river research and multispecies perspectives, specific moments in the river's environmental past and their place in social and political upheavals, and the emergence of ecologically attuned approaches in policy, behaviors, and cultural production.